RANCANG BANGUN MESIN PENGERING VERTIKAL DENGAN PENGADUKAN MEKANIK UNTUK BIJI-BIJIAN - Pribadyo Pribadyo (Program Studi Teknik Mesin Universitas Tarumanagara, 2018)
Abstract: The reduction of water content to a certain extent for cereals in the form of grain can be done through several methods, one of which is drying with heating. The purpose of this research is to design a prototype drying machine with a vertically screw-shaped mechanical screw. The drying machine is designed using heater and mixer working principles, wherein the heater is used for the drying process by engineering the heating air, while the mixer is used for the stirring system on the material to be dried. Tool design includes: Screw, Casing wire, Casing House and chassis. The wire casing design is based on the incoming heat flow rate and exhaust heat flow rate with the parameters of air velocity of entry and exit air velocity is known. The result of air velocity is 0.25 m2/s and the air velocity is 0.42 m2/s. Thus, the incoming heat flow rate is 0.5 kg/m3, and the outflow heat rate is 0.52 kg/m3. The volume of the contents of the wire casing of 7,5 kg/cm3. Screw designed with length (p) 60 cm, width of the upper arm (la) 28.8 cm, width of the forearm (lb) 22 cm. Wire casing is designed with length (p) 100 cm, width of upper arm (la) 50 cm, width of forearm (lb) 30 cm. The casing is designed with length (p) 100 cm, width of the upper arm (la) 70 cm, width of the forearm (lb) 50 cm, The chassis is designed with length (p) 107 cm, width of the upper arm (la) 77 cm and arm width Bottom (lb) 77 cm. And supported aids in the form of: Electric motor that serves as a driving force in the stirring system with a capacity of 450 rpm motor rotation is reduced with the transmission belt puly. Based on the results of the design has been successfully made prototype vertical dryer machine with mechanical stirring for grain.